Enhancing Interagency Coordination in Smart Bureaucracy for New Capital City: Case Study of Nusantara - Dana Indra Sensuse; Eko Yon Handri; Muhammad Mishbah; Rini Rachmawati; Wikan Danar Sunindyo; Galuh Syahbana Indraprahasta; Suet Leng Khoo; Khin Khin Soe (Human Behavior and Emerging Technologies)
The development of a new capital city presents complex challenges, especially in terms of the complicated bureaucratic flow in realizing an efficient, sustainable, and people-centered smart city as the new identity of a country. This study explores the complex issues faced in the development of Nusantara, the new capital city of Indonesia, and proposes a smart bureaucracy model to improve interagency coordination and transform modern bureaucratic processes. Using a hybrid methodological approach that combines soft systems methodology (SSM) with the TELOS framework and MoSCoW method, this study conducted extensive stakeholder interviews with officials from the Nusantara Authority, local governments, and academics, in addition to a comparative analysis with Putrajaya and Naypyidaw. This study produced a five-layer smart bureaucracy model consisting of strategic layers, interagency coordination, operations, monitoring and evaluation, and digital infrastructure. Implementation is structured in three phases: building basic elements through comprehensive regulations and a single authority; strengthening basic systems through the development of ICT infrastructure; and implementing advanced features, including a smart city platform. This model offers a comprehensive solution to improve interagency coordination through technology integration, considering organizational readiness and resource availability, and provides valuable insights for developing countries implementing similar initiatives in their national capitals.